Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1063/1.466745
|View full text |Cite
|
Sign up to set email alerts
|

Surface reaction kinetics of NO on Rh{110}

Abstract: The reaction of NO with Rh(110) single crystal surfaces was studied by means of various surface analytical tools including static secondary ion mass spectrometry (SSIMS), temperature programmed desorption (TPD), monochromatized x-ray photoelectron spectroscopy (MXPS), and ion scattering spectroscopy (ISS). Molecular NO adsorption was found to occur below 200 K. Higher temperatures caused dissociation of adsorbed NO molecules. Complete dissociation occurred only below a critical coverage, i.e., ΘNO≤0.12. Nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…In fact, it seems that preferential orientation of Rh surface on reduced ceria may also explain the specific role of CeOx surface. This is consistent with the fact that NO dissociation occurs at lower temperatures on Rh (110) and on Rh (100) than on Rh (111) [84,85].…”
Section: One Of the First Systematic Studies Of The No Reduction By Co Was Reported Bysupporting
confidence: 88%
“…In fact, it seems that preferential orientation of Rh surface on reduced ceria may also explain the specific role of CeOx surface. This is consistent with the fact that NO dissociation occurs at lower temperatures on Rh (110) and on Rh (100) than on Rh (111) [84,85].…”
Section: One Of the First Systematic Studies Of The No Reduction By Co Was Reported Bysupporting
confidence: 88%
“…At present we might postulate that the reason for the persistence of EXAFS visible Rh-Rh interactions might lie in the results of any dissociative adsorption of the NO [44,45] or subsequently, CO [46][47][48]. The products of any low level dissociation would be invisible to the mid range infrared and yet could quite easily act to curtail oxidative redispersion by adsorbing in high symmetry sites [48]effectively holding Rh atoms together and preventing their dispersion into monodisperse Rh nitrosyl or carbonyl species-or simply blocking the sites from whence oxidative disruption is promoted.…”
Section: Discussion Summary and Outlookmentioning
confidence: 98%
“…As described above, the NO decomposition on the small rhodium clusters is highly effective which was proved in theoretical and experimental studies. , ,,, However, as is well known, Rh is so expensive and limited in supply, hence there is a continued need to decrease the amount used in the three-way catalytic converters. An effective method is by doping other metals to reduce the amount of precious metal that has been used to improve the catalytic activity. , These results indicate that doping other atoms can increase the dissociative adsorption energy.…”
Section: Introductionmentioning
confidence: 94%
“…The reaction of the adsorption and reduction of NO on rhodium clusters and surfaces has received extensive attention in the areas of surface science. Size is one of the important parameters influencing the catalytic performance for most catalysts. , For instance, Rh particles have obvious size dependences, and the turnover number decreases gradually with the size decreasing in the reactions of CO + O 2 and CO + NO . The various chemisorption states of NO on Rh(111) and (100) surfaces had been studied with density functional theory (DFT), and the result revealed that the binding energy between NO molecules and Rh surfaces increased with the decrement of the coverages of NO .…”
Section: Introductionmentioning
confidence: 99%